La formación del quechua ecuatoriano: una nueva hipótesis - Itier, César (2021)
Since the studies of Alfredo Torero, Ecuadorian-Colombian Quechua is often considered to come from a variety that was formerly spoken on the central coast of Peru and introduced into Ecuador through maritime trade long before the formation of the Inca empire. Based on a dialectal comparison and an examination of historical sources, we refute this thesis and show that Northern Quechua is the product of a strong influence of Cuzco Quechua on the speech of the North Peruvian settlers that were brought by the Incas into Ecuador. Finally, this case study leads us to question the genetic classification of Quechua dialects proposed by Torero.